2021
DOI: 10.20944/preprints202109.0438.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Statistical Analysis of Dynamic Subgrid Modeling Approaches in Large Eddy Simulation

Abstract: In large eddy simulation (LES) of turbulent flows, the most critical dynamical processes to be considered by dynamic subgrid models to account for an average cascade of kinetic energy from the largest to the smallest scales of the flow is not fully clear. Furthermore, evidence of vortex stretching being the primary mechanism of the cascade is not out of the question. In this article, we study some essential statistical characteristics of vortex stretching and its role in dynamic approaches of modeling subgrid-… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…is found to be well correlated with the energy flux < ๐œ ๐‘–๐‘— ๐‘† ๐‘–๐‘— >; Fig. 1 supports the theoretical interpretation regarding the energy flux and viscous dissipation [8]. Indeed, the energy is transferred by large eddies to the subgrid-scale, which is dissipated at a rate of subgrid-scale dissipation, ๐œ€ ๐‘ ๐‘”๐‘  = 2๐œ— ๐œ ||๐‘†||.…”
Section: Validation Strategiessupporting
confidence: 81%
See 2 more Smart Citations
“…is found to be well correlated with the energy flux < ๐œ ๐‘–๐‘— ๐‘† ๐‘–๐‘— >; Fig. 1 supports the theoretical interpretation regarding the energy flux and viscous dissipation [8]. Indeed, the energy is transferred by large eddies to the subgrid-scale, which is dissipated at a rate of subgrid-scale dissipation, ๐œ€ ๐‘ ๐‘”๐‘  = 2๐œ— ๐œ ||๐‘†||.…”
Section: Validation Strategiessupporting
confidence: 81%
“…Finally, the second invariant rotation rate is getting by, The JPDF map between the second invariant (๐‘„ ๐บ ) and third invariant (๐‘… ๐บ ), and topological classification of local flow fields are shown in Fig. 2, see more detailed information [8], [15], [16]. The region of Fig.…”
Section: Joint Probability Density Function (Jpdf) Of Sgs Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is equivalent to mimicking the effects of dynamical variations of C s (x, t) via the stretching of vortices. Based on LES of decaying homogeneous isotropic turbulence for Reynolds numbers up to 10 8 (using the localized dynamic Smagorinsky model [34]), we found that c k = 0.325 ยฑ 0.035. Thus, a fixed value of c k = 0.325 is considered in this article.…”
Section: Vortex-stretching Based Scale-adaptive Subgrid Modelmentioning
confidence: 93%
“…Note that the subgrid model Eq (9) implicitly adapts the energy flux as the characteristic length scale of turbulence dissipation varies locally. Recent work of [34,15,35] evaluated the scaleadaptive LES model, Eq (9), in the case of isotropic turbulence, and atmospheric boundary layer flow over urban and hilly terrain. In this research, we consider an improved actuator disk model and show that our scale-adaptive LES method adequately captures the near turbine dynamics.…”
Section: Vortex-stretching Based Scale-adaptive Subgrid Modelmentioning
confidence: 99%